Mitigating U.S. Undergraduates' Attitudes Toward International Teaching Assistants. Issue 4 (27th August 2014) - Kang, Okim; Rubin, Donald; Lindemann, Stephanie
Abstract : Intelligibility problems between native speakers (NSs) and nonnative speakers (NNSs) of English are often attributed to some perceived inadequacy of the NNSs. This emphasis on the NNSs' role in successful communication is highly problematic, given that intelligibility is a negotiated process between speaker and listener. In some cases, NSs have negative attitudes toward NNSs that impair their willingness to communicate with NNSs and to acknowledge proficient NNS speech. Thus, NS attitudes are also important factors in the success of NS–NNS communication. This article demonstrates a brief intervention that reduces negative language attitudes and thus promotes communication between NS undergraduates and NNSs who are international teaching assistants (ITAs). Two studies are reported. In both, undergraduates engaged in cooperative problem‐solving exercises with ITAs. Results show that undergraduates exposed to structured intergroup contact subsequently rated ITAs higher in instructional competence and comprehensibility. Future applications of contact theory promise to improve NSs' comprehension of nonnative English and to cultivate their global citizenship.